Channel formation and visualization of melting and crystallization behaviors in direct‐contact latent heat storage systems. (12th February 2020) - Kunkel, Sven; Schütz, Philipp; Wunder, Frederik; Krimmel, Stefan; Worlitschek, Jörg; Repke, Jens‐Uwe; Rädle, Matthias
Summary: Thermal storage systems are an essential component for increasing the share of renewable energies in residential heating and for the valorization of waste heat. A key challenge for the widespread application of thermal storage systems is their limited power‐to‐capacity ratio. One potential solution for this challenge is represented by direct‐contact latent heat storage systems, in which a phase change material (PCM) is in direct contact with an immiscible heat transfer fluid (HTF). To demonstrate the applicability of the direct‐contact concept for domestic hot water production, a PCM with a phase change temperature of 59°C is chosen. To enable cost‐efficient implementation of the storage system, a eutectic mixture of two salt hydrates, magnesium chloride hexahydrate and magnesium nitrate hexahydrate, is chosen as the PCM. One key aspect for the direct‐contact concept is that, during discharge, the HTF channels in the PCM do not become clogged during the solidification of the PCM. In this study, the formation and topology of the channels in direct‐contact systems under an optimized flow condition are investigated via visual observation and X‐ray computed tomography. The elucidation of the channel structure provides information on the melting and crystallization behaviors of the PCM, which are shown schematically. Abstract : In this study, the melting and solidification behaviors of a phase change material (PCM) within a direct‐contact latent heat storage system were experimentally investigated and visualized. The PCM is in direct contact with an immiscible heat transfer fluid (HTF). The considered system consisted of a vertical cylindrical storage tank containing a eutectic mixture of two salt hydrates as the PCM and a mineral oil as the HTF flowing through an orifice at the bottom of the storage tank. By combining visual observations with a volumetric cross‐sectional analysis by X‐ray CT, the melting and solidification behaviors were elucidated, and design principles for such storage systems were visualized, derived, and proposed.